Corporate identity pillars in a Malaysian government-linked company's (GLC) corporate brand: upper management views - Bidin, Rosmiza (Faculty of Communication Arts, Chulalongkorn University, 2015)
Corporate identity of the government–linked companies: Government linked company play an important role in economic development, especially in developing nations. However, experience of many countries demonstrates that GLCs are usually less efficient than non-GLCs as measured by their economic performance. Since the Malaysian government had introduced the GLC transformation programme in 2004 to improve GLC’s performance, it is, therefore, imperative to investigate GLC’s corporate identity from the managerial perspective. The purpose of this study is to investigate upper management perception on the elements of corporate identity pillars in managing CIMB corporate brand. This study focuses on the elements of corporate identity pillars namely the subjective pillars and physical infrastructure of corporate identity. The management perception on corporate identity is derived from the in-depth interviews with the upper management and their strategy in communicating identity through annual reports and photographs. The upper management corporate identity conception process starts with the identity pillars (Melewar and Karaosmanoglu, 2006; Balmer, 2002; Balmer and Soenen, 1997; Birkigt and Stadler, 1986), where the subjective pillars and physical infrastructures of a particular corporate identity are considered. Two subjective pillars were frequently discussed in the literature namely corporate culture (Van Riel and Balmer, 1997;) and corporate personality (Balmer, 1995). Two physical infrastructures were frequently discussed in the literature namely the organizational structure and brand structure (Melewar and Karaosmanoglu, 2006). This information is very useful and acts as a basis that helps the organisation to understand the context in which the whole strategy is built. This study employed qualitative, case study method where the Chief Executive Officer and the Vice President of Corporate Communication were interviewed. Organisational documents (six years annual reports and photographies) were also used to triangulate the data. Result confirmed that the GLC’s upper management perceptions on the elements of corporate identity pillars were parallel to the literature. We also introduced newly emerging factor, the role of government, in influencing corporate identity process. The study of corporate identity elements from the perception of management in Asia, particularly in Malaysia is limited. Therefore, this study filled the gap and enriched the data on the understanding of corporate identity elements in Malaysia. We chose to study government link in Malaysia because government linked company play an important role in economic development, especially in developing nations. Since the government had introduced the GLC transformation programme to improve GLC’s performance, it is, therefore, imperative to investigate GLC’s corporate identity from the managerial perspective.